Effect of heat treatment on the molecular mobility in the triacylglycerol - Лазаренко, Михайло Васильович; Баглюк, Сергій Володимирович (Eastern-European Journal of Enterprise Technologies, 2014)
Relevance of the work is caused by the widespread introduction of new technologies in the food industry processes, requiring the use of modern techniques for the quality analysis of products at all stages of their processing and storage. Therefore, the purpose of the paper is to study the physicochemical properties of refined sunflower oil to select rational modes of cooking healthy foods. Thermophysical and dielectric properties of a number of refined sunflower oil samples with different thermal history were investigated. The samples were kept in an air thermostat at isobaric conditions at heat treatment temperature of 433K. Temperature dependences of oil specific heat in the temperature range 173 - 423K were obtained by the thermophysical method on dynamic calorimeter with a heating rate of 3K/min. Complex permittivity of oil samples in the temperature range 173 - 323K at frequencies f = 1, 5, 10, 50kHz was studied using an automated system based on AC Bridge R5083. Molecular mobility and nature of relaxation and phase transitions was considered and, based on this, the changes in the structure and chemical composition of sunflower oil as a result of heating in the normal use conditions were studied. This is of great applied importance since under these conditions (at T > 373K in air) processes of thermal and thermooxidative degradation of oil with the formation of harmful substances (fatty acid peroxides, acrolein, etc.) that can go into food are possible.